Poetic Inquiry: A Fierce, Tender, and Mischievous Relationship with Lived Experience - Sean Wiebe (Language and Literacy: A Canadian Educational e-journal, 2015)
Common to poetic inquirers is a sensitivity to the ways traditional qualitative analysis can systematize and simplify, oftentimes generating theories and practices that are out of kilter with our intuitive experience of being in the world. In this paper I look at how the richness of lived experience can be sustained in poetic inquiry,  and in so doing, offer the terms fierce, tender, and mischievous as qualities of engagement that are often exemplified in the ways poetic inquirers live and work.